Surveillance and Control of Antibiotic Resistance in the Mediterranean Region - Ricciardi, Walter (Mediterr J Hematol Infect Dis, 2016)
Antibiotic resistance is one of the most relevant problems in the healthcare: the growth of resistant microorganisms in healthcare settings is a worrisome threat, raising length to stay (LOS), morbidity and mortality in those patients. The importance of the antibiotic resistance and its spread around the world, gave rise to the activation of several surveillance systems, based especially on the collection of laboratory data to local or national level. The objective of this work is to carry out a review of the scientific literature existing on the topic and scientific activities related to surveillance of antibiotic resistance in the countries bordering the Mediterranean Sea. Recent Data from European Centre for Disease Prevention and Control (November 2015) show, for different combinations bacterium-drug, an increase of resistance from North to South and from West to East of Europe. It is of particular concern the phenomenon of resistance carried out by some gram-negative, specifically Klebsiella pneumoniae and Escherichia coli to third-generation cephalosporin, often combined in opposition to fluoroquinolones and aminoglycosides. Is particularly high the incidence of resistance to carbapenems by strains of Enterobacteriaceae (Klebsiella included). The resistance exerted by MRSA (Methicillin-resistant Staphylococcus aureus) continues to be relevant, albeit showing some decline in recent years. The incidence of resistance carried on by Streptococcus pneumoniae is stable and is mainly relevant to macrolides. Finally, a significant increase in recording relatively exercised by Enterococcus faecium to Vancomycin. Detecting, preventing, and controlling antibiotic resistance requires strategic, coordinated, and sustained efforts. It also depends on the engagement of governments, academia, industry, healthcare providers, the general public, and the agricultural community, as well as international partners. Committing to combating antibiotic-resistant microbes does support patient care, economic growth, agriculture, and economic and national security.